THE SIGNIFICANCE OF DEVIATION AND REPITITION IN LANGUAGE (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
This article explores the pivotal roles played by deviation and repetition in the framework of language, delineating their significance across various linguistic levels. It begins by defining deviation as the deliberate departure from conventional linguistic patterns and repetition as the recurrence of linguistic elements. The article then proceeds to examine the different types of deviation and repetition, highlighting their manifestations in phonemic, morphemic, syntactic, and semantic contexts. In discussing deviation, the article elucidates its presence in altering phonemic sounds, morphemic structures, and its role in enhancing language creativity and emphasis. It emphasizes how deviation contributes to the richness and diversity of language by breaking away from standard linguistic norms. The article meticulously elaborates on various types of repetition, elucidating phonemic repetition involving sounds, morphemic repetition with affixation and reduplication, syntactic repetition encompassing structures, and semantic repetition dealing with meaning and concepts. Each type is exemplified with illustrative instances, demonstrating how repetition reinforces ideas, aids memorability, and contributes to the aesthetic and communicative value of language.